Brand Postcolonial. 'Third World' Texts and the Global - Nayar, Pramod K. (De Gruyter, 2019)
This book studies the making of the postcolonial author and text as a brand. It examines specific themes, wherein the postcolonial text acquires global visibility, even determining the nature of global debates: the authenticity of representing 'native' cultures, subalternity, indigeneity, and humanism. It studies the circulation of the postcolonial as literary-ethnic chic and the author as a globally mobile celebrity.